2016
DOI: 10.1038/srep36557
|View full text |Cite
|
Sign up to set email alerts
|

Underwater superoleophobicity, anti-oil and ultra-broadband enhanced absorption of metallic surfaces produced by a femtosecond laser inspired by fish and chameleons

Abstract: Reported here is the bio-inspired and robust function of underwater superoleophobic, anti-oil metallic surfaces with ultra-broadband enhanced optical absorption obtained through femtosecond laser micromachining. Three distinct surface structures are fabricated using a wide variety of processing parameters. Underwater superoleophobic and anti-oil surfaces containing coral-like microstructures with nanoparticles and mount-like microstructures are achieved. These properties of the as-prepared surfaces exhibit goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…To be on the safe side, they must avoid contamination and be not discovered in shallow seas or in air by radar. After femtosecond laser ablation, Yin et al formed coral‐like microstructures on the stainless steel surface, as shown in Figure a,b . There are a large number of cavities with the diameter of 3–10 µm randomly covering on the treated surface.…”
Section: Functions and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be on the safe side, they must avoid contamination and be not discovered in shallow seas or in air by radar. After femtosecond laser ablation, Yin et al formed coral‐like microstructures on the stainless steel surface, as shown in Figure a,b . There are a large number of cavities with the diameter of 3–10 µm randomly covering on the treated surface.…”
Section: Functions and Applicationsmentioning
confidence: 99%
“…e,f) Schematic of the potential application of the femtosecond‐laser‐treated metal surface on a submarine: the effect of e) an untreated flat metal surface and f) a laser‐induced rough metal surface on the oil wettability and light reflectance in a water medium. Reproduced with permission . Copyright 2016, Springer Nature.…”
Section: Functions and Applicationsmentioning
confidence: 99%
“…Besides, a facile route for the fabrication of these materials can make them more promising in practical oil/water separation. 2830…”
Section: Introductionmentioning
confidence: 99%
“…Under-water superoleophobicity has been generated on the metallic surfaces, through femtosecond laser micromachining [6]. The surfaces generated through this method contained coral-like microstructures with nanoparticles which showed sustained chemical stability when exposed to various oils and also while immersed in water with different pH values.…”
Section: Introductionmentioning
confidence: 99%